The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.ejhg.5201814
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to chromosome 11p12 in two Maltese families with a highly penetrant form of osteoporosis

Abstract: Osteoporosis is a metabolic bone disease with a strong genetic component. Family-based linkage studies were performed by a number of investigators to try to identify loci that might contain genes responsible for an increased susceptibility to osteoporosis. A whole-genome linkage scan using 400 microsatellite markers was performed in 27 members from two Maltese families with a highly penetrant form of osteoporosis. The phenotype was defined by lumbar and femoral z-scores calculated after measurement of bone min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Only 3 A alleles were identified in 3 heterozygous individuals, thus giving a population frequency of 2.38% and a minor allele frequency of 0.012 (1.19%). None of the nine affected members from the other pedigree (Pedigree 1), used in the previous linkage study [5], was found to carry the A allele. Fig.…”
Section: Sequencing Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Only 3 A alleles were identified in 3 heterozygous individuals, thus giving a population frequency of 2.38% and a minor allele frequency of 0.012 (1.19%). None of the nine affected members from the other pedigree (Pedigree 1), used in the previous linkage study [5], was found to carry the A allele. Fig.…”
Section: Sequencing Resultsmentioning
confidence: 96%
“…In a previous linkage study, performed on two Maltese families with a high incidence of osteoporosis, suggestive linkage to chromosome 11p12 was observed [5]. Fine-mapping reduced the linkage interval to a region between markers D11S1392 (50.64 cM) and D11S935 (52.94 cM), with highest total heterogeneity LOD and NPL (3.07 and 7.0, respectively) to marker D11S935.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations